The Role of Family Life and the Influence of Peer Pressure on Delinquency: Qualitative Evidence from Malaysia - Ezarina Zakaria; Noor Nasihah Kamarudin; Zhooriyati Sehu Mohamad; Masahiro Suzuki; Balan Rathakrishnan; Soon Singh Bikar Singh; Zaizul Ab Rahman; Vikneswaran Sabramani; Azianura Hani Shaari; Mohammad Rahim Kamaluddin (MDPI, 2022)
Juvenile delinquency is always seen as a public health problem which needs intervention at various levels. Identifying which factors may lead juveniles to delinquency is a long-standing question among criminologists. This remains the case in Malaysia. There are studies that have explored the impact of problem-solving skills, low socioeconomic status, and gender differences in predicting the delinquent behavior of youth in Malaysia. However, very few studies have aimed to find an in-depth understanding of the effects of family roles and peer pressure on delinquency in Malaysia. The present qualitative research was designed to fill this gap in the literature. In-depth interviews were conducted with 12 young male prisoners (juvenile delinquents) in Malaysia to explore the influences of family life and peer pressure on delinquency. The current study showed that parental un-involvement, parent separation, peer pressure, criminal gang membership, and parents’ involvement in crime were the important factors for involvement in delinquency. The findings revealed the importance of guidance and counseling for parents and adolescents, to help them cope with life challenges and to build their social and emotional skills, as well as the necessity of appointing school psychologists and public health experts to help the youths become valuable individuals.